Imperial China’s Border Control Law - Edwards, R. Randle (Columbia Journal of Asian Law, 1987)
The passage of persons, things, and even ideas across China’s land and sea boundaries was subject to a comprehensive network of rules promulgated by the Qing state (1644-1911) and its predecessors. This intricate regulatory system was of functional importance in the management of China’s relations with foreign countries, and it offers rich food for comparative thinking about the evolution of rules for interstate conduct. Yet this normative system has largely escaped study, in part because law was never highly regarded by the official chroniclers of Chinese history and in part because the rules themselves are widely scattered throughout the numerous compendia of laws and regulations. This article will introduce and examine the border control regulations and procedures of the Qing Dynasty. Selected cases will be used to illustrate the dynamic process of interstate lawmaking in China’s relations with some of its East Asian neighbors in the later imperial era.